2020
DOI: 10.1186/s12893-020-00804-w
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent broad ligament leiomyosarcoma with pancreatic and thigh metastasis: a case report

Abstract: Background: Leiomyosarcoma (LMS) is an uncommon mesenchymal neoplasm, which infrequently metastasizes to pancreas and thigh. Clinical presentation and imaging findings of metastatic broad ligament LMS are often nonspecific. Complete excision plays an important role in treatment of patients with localized LMS. Case presentation: Here, we report a case of a 33-year-old woman with recurrent broad ligament LMS metastasizing to pancreas and thigh. Previously, she was diagnosed with broad ligament LMS and underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Here, the last term was the most important. LMS of the broad ligament is very rare with only 33 cases reported in English literature to date [1][2][3][4][5][6][7][8]. It has been reported that broad ligament LMS metastasis sites include the stomach, pancreas, and neck region[6-8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the last term was the most important. LMS of the broad ligament is very rare with only 33 cases reported in English literature to date [1][2][3][4][5][6][7][8]. It has been reported that broad ligament LMS metastasis sites include the stomach, pancreas, and neck region[6-8].…”
Section: Discussionmentioning
confidence: 99%
“…According to the numbers of MFs and the degree of cell differentiation, LMS is divided into well, intermediate and poor differentiation. Positive staining of the immunohistochemical markers Desmin and SMA contributed to the diagnosis [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation